Utilisation of a smartphone-enabled video otoscope to train novices in otological examination and procedural skills. Issue 4 (13th April 2022) - Navaratnam, A V; Halai, A; Chandrasekharan, D; Mistry, R; Rogel-Salazar, J; Manjaly, J G; Tatla, T; Singh, A; Ramdoo, K
Abstract: Objective: The ai/m of this study was to compare the self-reported confidence of novices in using a smartphone-enabled video otoscope, a microscope and loupes for ear examination and external ear canal procedures. Method: Medical students ( n = 29) undertook a pre-study questionnaire to ascertain their knowledge of techniques for otoscopy and aural microsuction. Participants underwent teaching on ear anatomy, examination and procedural techniques using a microscope, loupes and smartphone-enabled video otoscopes. Confidence and preference using each modality was rated using a Likert-like questionnaire. Results: After teaching, all modalities demonstrated a significant increase in confidence in ear examination ( p < 0.0001). Confidence in using the smartphone-enabled otoscope post-teaching was highest ( p = 0.015). Overall, the smartphone-enabled video otoscope was the preferred method in all other parameters assessed including learning anatomy or pathology (51.72 per cent) and learning microsuction (65.51 per cent). Conclusion: Smartphone-enabled video otoscopes provide an alternative approach to ear examination and aural microsuction that can be undertaken outside of a traditional clinical setting and can be used by novices.